PESANTREN DAN KEPEMIMPINAN KYAI - KESUMA, GUNTUR CAHAYA (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2014)
Pesantren is an educational institution that cannot be separated from religious scholars as a figure of a leader. Progress or setbacks of Pesantren is determined by figure of Kyai as a central figure in the boarding school. Thus, Pesantren and Kyai have a relationship of mutual influence. Pesantren is able to develop due to figure of Kyai who can lead well. Conversely, if Pesantren did not develop, it means that Kyai cannot lead well. This paper is intended to explain the relationship between Pesantren and the leadership of Kyai